How age and linguistic competence alter the interplay of perceptual and cognitive factors when listening to conversations in a noisy environment - Avivi-Reich, Meital; Daneman, Meredyth; Schneider, Bruce A. (Frontiers in Systems Neuroscience, 2014)
Multi-talker conversations challenge the perceptual and cognitive capabilities of older adults and those listening in their second language (L2). In older adults these difficulties could reflect declines in the auditory, cognitive, or linguistic processes supporting speech comprehension. The tendency of L2 listeners to invoke some of the semantic and syntactic processes from their first language (L1) may interfere with speech comprehension in L2. These challenges might also force them to reorganize the ways in which they perceive and process speech, thereby altering the balance between the contributions of bottom-up versus top-down processes to speech comprehension. Younger and older L1s as well as young L2s listened to conversations played against a babble background, with or without spatial separation between the talkers and masker, when the spatial positions of the stimuli were specified either by loudspeaker placements (real location), or through use of the precedence effect (virtual location). After listening to a conversation, the participants were asked to answer questions regarding its content. Individual hearing differences were compensated for by creating the same degree of difficulty in identifying individual words in babble. Once compensation was applied, the number of questions correctly answered increased when a real or virtual spatial separation was introduced between babble and talkers. There was no evidence that performance differed between real and virtual locations. The contribution of vocabulary knowledge to dialogue comprehension was found to be larger in the virtual conditions than in the real whereas the contribution of reading comprehension skill did not depend on the listening environment but rather differed as a function of age and language proficiency. The results indicate that the acoustic scene and the cognitive and linguistic competencies of listeners modulate how and when top-down resources are engaged in aid of speech comprehension.